2012
DOI: 10.1155/2012/103032
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Late Mortality and Second Malignant Neoplasms among 5-Year Survivors of Young Adult Cancer: A Report of the Childhood, Adolescent, and Young Adult Cancer Survivors Research Program

Abstract: We conducted a population-based retrospective study to assess the long-term risks of overall and cause-specific mortality and second malignant neoplasm (SMN) among survivors of young adult cancer compared to the risk in British Columbia (BC) population and to evaluate the effects of demographic and clinical factors on risk. 1248 5-year survivors of young adult cancer diagnosed 1970–1995 between 20 and 24 years of age were identified from the BC Cancer Registry and followed to the end of 2007. Standardized mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 32 publications
(49 reference statements)
1
41
0
Order By: Relevance
“…4,6,8,9 Moreover, our slightly lower overall SMR of 4.2 in young adult cancer survivors resembled earlier results, which were between 4.6 and 5.9. 10,11 The somewhat lower figures in our study may result from including the most recent treatment periods with possibly improved therapy regimens and from the effect of older attained age due to our very long follow-up. Cardiovascular disease was associated with the second highest non-cancer related SMRs after infectious diseases.…”
Section: Epidemiologymentioning
confidence: 58%
See 1 more Smart Citation
“…4,6,8,9 Moreover, our slightly lower overall SMR of 4.2 in young adult cancer survivors resembled earlier results, which were between 4.6 and 5.9. 10,11 The somewhat lower figures in our study may result from including the most recent treatment periods with possibly improved therapy regimens and from the effect of older attained age due to our very long follow-up. Cardiovascular disease was associated with the second highest non-cancer related SMRs after infectious diseases.…”
Section: Epidemiologymentioning
confidence: 58%
“…[4][5][6][7][8][9] Only few studies have investigated those topics for the survivors of young adult (YA) cancer patients aged from 20 to 34 years at cancer diagnosis. [10][11][12] Previous studies have found elevated risks for chronic health conditions which contribute to higher mortality among survivors of childhood cancer patients compared to the general population. 5,9,13,14 Patterns of increased excess mortality after childhood cancer have been shown to be dependent on time from cancer diagnosis and cause of death.…”
mentioning
confidence: 99%
“…When we examined the hospital diagnosis, leukemia survivors experienced blood diseases more often than the comparison cohort, whereas lymphoma and CNS survivors were hospitalized for neoplasms more often. For these cancers, by 5 years after diagnosis, although the risk of relapse is still high, the risk of second cancers becomes increasingly common (16, 20). Although we were unable to evaluate specific conditions leading to this morbidity risk, both lymphoma and CNS tumor survivors may be hospitalized because of treatment for recurrences, metastatic disease, and/or second cancers, suggesting the need for better surveillance to detect second malignancies in earlier stages.…”
Section: Discussionmentioning
confidence: 99%
“…The types of secondary neoplasms in these patients includes hematologic malignancies (acute myeloid leukemia, myelodysplastic syndrome and non-Hodgkin lymphoma), brain tumors and other solid carcinomas. This risk is likely to be the consequence of multiple factors, including environmental factors and genetic susceptibility related to the primary diagnosis, radiotherapy, family history of cancer, immunosuppression, and hormonal factors [1236]. …”
Section: Discussionmentioning
confidence: 99%